In vitro Clonal Propagation of Vitex negundo L.-An Important Medicinal Plant (Plant Tissue Culture and Biotechnology, 2010)
Vitex negundo L., a perennial shrub belonging to the family Verbenaceae, is an important medicinal plant. It grows abundantly in St. Martin’s Island and commonly known as Nishinda. Generally leaf is used for medicinal purpose but root, flower and fruit also have the medicinal values (Hasan 1982). Leaf of the plant contains essential oil, an alkaloid, nishindin. Stem and bark contain flavonoid glycosides. Leaves of nishinda very effectively reduce the inflamma-tory swellings of joints in rheumatic attacks. Juice of fresh leaf removes fetid discharges and worms from ulcers. Flower oil is applied to sinuses and scrofulous sores. Root juice is tonic, expectorant and diuretic (Ghani 1998).        Tissue culture has greatly enhanced the scope and potentiality of mass propagation by exploiting the regenerative behavior in a wide range of selected horticultural and agricultural plants including the medicinal ones (Roy et al. 1994, Thiruvengadam and Jayabalan 2000, Islam et al. 2001 and Jawahar et al. 2008). Keeping in mind the medicinal importance of all the parts of this plant, an attempt has been made to formulate its regeneration system through in vitro culture.  Key words: Vitex negundo, medicinal plant, Clonal propagation D.O.I. 10.3329/ptcb.v19i1.5005 Plant Tissue Cult. & Biotech. 19(1): 113-117, 2009 (June) –Short Communication